First annual Meeting Report: meeting of the European Diphtheria Surveillance Network, Stockholm, 17 March 2011 - European Center for Disease Control and Prevention (2018)
European Diphtheria Surveillance Network: Participant (Portugal) - Paula Lavado (Departamento de Doenças Infeciosas, INSA)